PERCEPTIONS OF ENGLISH EDUCATION STUDENTS TOWARDS COOPERATIVE LEARNING IN LEARNING ENGLISH AT MUHAMMADIYAH UNIVERSITY OF MUARA BUNGO - Dhea Aura Cindyana; Kurniawan, Ridho; Habibah, Nur (Journal Of Language Education and Development (JLed), 2025)
Cooperative learning has become a key pedagogical approach in English education, with group discussion as its primary implementation. This study aims to explore English Education students' perceptions of cooperative learning through group discussion activities at Muhammadiyah University of Muara Bungo. Using a qualitative phenomenological approach, this study involved five students from different cohorts selected purposively. Data were collected through semi-structured interviews and analyzed using thematic analysis based on the five basic elements of cooperative learning theory. The findings indicate that students demonstrate high awareness of positive interdependence and individual accountability, recognizing the collective nature of success. They prefer small-group formats and value promotive interaction, especially the "learning by teaching" phenomenon. Students develop interpersonal and conflict-resolution skills, though communication skills still require improvement. Group processing emerges as the least systematically applied element. The study recommends implementing more structured group processing and systematic training in cooperative learning principles.